Human surfactant protein A inhibits SARS-CoV-2 infectivity and alleviates lung injury in a mouse infection model - Jacob, Ikechukwu B.; Gemmiti, Amanda; Xiong, Weichuan; Reynolds, Erin; Nicholas, Brian; Thangamani, Saravanan; Jia, Hongpeng; Wang, Guirong (Frontiers in Immunology, 2024)
SARS coronavirus 2 (SARS-CoV-2) infects human angiotensin-converting enzyme 2 (hACE2)expressing lung epithelial cells through its spike (S) protein. The S protein is highly glycosylated and could be a target for lectins. Surfactant protein A (SP-A) is a collagen-containing C-type lectin, expressed by mucosal epithelial cells and mediates its antiviral activities by binding to viral glycoproteins. This study examined the mechanistic role of human SP-A in SARS-CoV-2 infectivity and lung injury in vitro and in vivo. Results showed that human SP-A can bind both SARS-CoV-2 S protein and hACE2 in a dose-dependent manner (p<0.01). Pre-incubation of SARS-CoV-2 (Delta) with human SP-A inhibited virus binding and entry and reduced viral load in human lung epithelial cells, evidenced by the dose-dependent decrease in viral RNA, nucleocapsid protein (NP), and titer (p<0.01). We observed significant weight loss, increased viral burden, and severe lung injury in SARS-CoV-2 infected hACE2/SP-A KO mice (SP-A deficient mice with hACE2 transgene) compared to infected hACE2/mSP-A (K18) and hACE2/hSP-A1 (6A 2 ) mice (with both hACE2 and human SP-A1 transgenes) 6 Days Post-infection (DPI).Furthermore, increased SP-A level was observed in the saliva of COVID-19 patients compared to healthy controls (p<0.05), but severe COVID-19 patients had relatively lower SP-A levels than moderate COVID-19 patients (p<0.05). Collectively, human SP-A attenuates SARS-CoV-2induced ALI by directly binding to the S protein and inhibiting its infectivity, and SP-A level in the saliva of COVID-19 patients might serve as a biomarker for COVID-19 severity.